Containment studies of transgenic mosquitoes in disease endemic countries: The broad concept of facilities readiness - Quinlan, M. Megan; Birungi, Josephine; Coulibaly, Mamadou B.; Diabaté, Abdoulaye; Facchinelli, Luca; Mukabana, Wolfgang R.; Mutunga James M.; Nolan, Tony; Raymond, Peter; Traoré, Sékou F. (Mary Ann Liebert Inc, 2018)
Genetic strategies for large scale pest or vector control using modified insects are not yet operational in Africa, and currently rely on import of the modified strains to begin preliminary, contained studies. Early involvement of research teams from participating countries is crucial to evaluate candidate field interventions. Following the recommended phased approach for novel strategies, evaluation should begin with studies in containment facilities. Experiences to prepare facilities and build international teams for research on transgenic mosquitoes revealed some important organizing themes underlying the concept of “facilities readiness,” or the point at which studies in containment may proceed, in sub-Saharan African settings. First, “compliance” for research with novel or non-native living organisms was defined as the fulfillment of all legislative and regulatory requirements. This is not limited to regulations regarding use of transgenic organisms. Second, the concept of “colony utility” was related to the characteristics of laboratory colonies being produced so that results of studies may be validated across time, sites, and strains or technologies; so that the appropriate candidate strains are moved forward toward field studies. Third, the importance of achieving “defensible science” was recognized, including that study conclusions can be traced back to evidence, covering the concerns of various stakeholders over the long term. This, combined with good stewardship of resources and appropriate funding, covers a diverse set of criteria for declaring when “facilities readiness” has been attained. It is proposed that, despite the additional demands on time and resources, only with the balance of and rigorous achievement of each of these organizing themes can collaborative research into novel strategies in vector or pest control reliably progress past initial containment studies.